Sistema de arquivos da UFSM: a capacitação profissional em gestão arquivística na modalidade à distância - Bello, Rosilaine Zoch (2013)
This main goal of this project was to implement a training course in archivistic to the Technical and Administrative Servers in Education of the UFSM using as a technological tool the Learning Management System Moodle. The intention is produce a reflection about the modality of distance learning and the LMS as an element to support a professional training in the institution. The research was classified as applied quantitative approach and a case study through the technical procedures for acquiring objective knowledge about Moodle; the study supports a proposal and an evaluation of an alternative training using distance learning. Techniques and instruments of literature were used for read, analyze and interpret the last material already published in books, scientific papers, dissertations and doctoral theses. The bibliography facilitated the planning and the development of a training course in distance learning using the LMS of the Pró-Reitoria de Gestão de Pessoas (PROGEP) in the UFSM university. To reinforce the requirements for the expansion of the institutional archivistics polices of the university, the project develops studies in university archives and in the document preservation as an evidence of scientific, cultural and educational knowledge of the country. This helps to ensure the right access to information, the right of citizens and transparency of government actions. The project demonstrated the feasibility of conducting distance learning training courses to servicemen directly or indirectly involved in institutional documents management. The staff improvement policies implementation through distance learning is an effective strategic tool to implement the UFSM archivistic system. The LMS Moodle of PROGEP worked as environment of cooperative interaction between technical and administrative servicemen and the DAG (Departamento de Arquivo Geral).